DETERMINAN KINERJA PENGELOLAAN KEUANGAN DESA DI KABUPATEN KAMPAR - Burhanuddin; Alfurkaniati; Rahmat Ismael yunef (Journal Of Islamic Finance And Accounting Research, 2023)
This research was conducted in villages in Gunung Sahilan District, Kampar Regency, with the aim of research to determine the Effect of Transparency, Accountability, Role of Village Apparatus, Community Participation and Effectiveness of Village Financial Management Performance, (Empirical Study on Villages in Gunung Sahilan District, Kampar Regency). This research is part of a quantitative research that is correlational. The data used are primary data with data collection techniques used are questionnaires and data analysis techniques using multiple regression methods. The results obtained indicate that partially and simultaneously the variables of Transparency, Accountability, Role of Village Apparatus, Community Participation and Effectiveness have a positive and significant effect on Village Financia lmanajement Performent.